2022
DOI: 10.1002/rth2.12769
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in venous thromboembolism: A surveillance program in Durham County, North Carolina

Abstract: Background: Venous thromboembolism (VTE) affects approximately 1-2 individuals per 1000 annually and is associated with an increased risk for pulmonary hypertension, postthrombotic syndrome, and recurrent VTE. Objective: To determine risk factors, incidence, treatments, and outcomes of VTE through a 2-year surveillance program initiated in Durham County, North Carolina (population approximately 280,000 at time of study). Patients/Methods: We performed a retrospective analysis of data actively collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 70 publications
(119 reference statements)
1
6
0
Order By: Relevance
“…In Saber et al, authors found that Black patients had a higher incidence of VTE and were noted to be younger than their White counterparts ( P < .0001). 7 Similarly, our study revealed that individuals who exhibited severe body injuries and received early VTE prophylaxis were predominantly from the Black demographic and were of a younger age group. This trend is further substantiated by Zebley et al, whose research demonstrated that Black patients had the highest rates of VTE prophylaxis utilization, coupled with the shortest time to administration (1.6 days) 3 .…”
Section: Discussionsupporting
confidence: 51%
“…In Saber et al, authors found that Black patients had a higher incidence of VTE and were noted to be younger than their White counterparts ( P < .0001). 7 Similarly, our study revealed that individuals who exhibited severe body injuries and received early VTE prophylaxis were predominantly from the Black demographic and were of a younger age group. This trend is further substantiated by Zebley et al, whose research demonstrated that Black patients had the highest rates of VTE prophylaxis utilization, coupled with the shortest time to administration (1.6 days) 3 .…”
Section: Discussionsupporting
confidence: 51%
“…We identified patients with a history of VTE at Duke University Hospital, Duke Regional Hospital, and the Durham Veterans’ Administration Medical Center within Durham County, North Carolina. Patients were included if they resided within Durham County at the time of diagnosis of VTE between April 1, 2012, and March 31, 2014 [ 6 ]. Deep venous thrombosis (DVT) and pulmonary embolism (PE) were searched by International Classification of Diseases, Ninth Revision (ICD-9) and Current Procedural Terminology (CPT) codes during the surveillance period.…”
Section: Methodsmentioning
confidence: 99%
“…All cases identified by electronic medical record screening were confirmed by review of imaging studies, autopsy reports, or clinical records by trained research staff and clinicians. Consistent with our previous paper, patients living outside Durham County at time of diagnosis, or at time of death for autopsy cases, were not included [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations